Inhibitory brainstem reflexes under external emotional-stimuli in bipolar I and II disorders - Zhu, Qisha; Wang, Jiawei; Shen, Chanchan; Fan, Hongying; Zhang, Bingren; Ma, Guorong; Lu, Yanxia; Wang, Wei (BMC psychiatry, 2017)
Bipolar disorder types I (BD I) and II (BD II) might present different dysfunctions of the cortex and brainstem, as reflected by the second exteroceptive suppression period of temporalis muscle activity (ES2) under different stimuli of external emotions. This study included 30 BD I and 20 BD II patients, and 40 healthy volunteers. All participants were invited to answer the Mood Disorder Questionnaire, the Hypomania Checklist-32, and the Plutchik-van Praag Depression inventory, as well as to undergo the ES2 test under external emotional-stimuli (emotional pictures plus sounds) of Disgust, Erotica, Fear, Happiness, and Sadness. The scale scores were elevated in both patient groups, but were not correlated with ES2 parameters. Compared to healthy controls, BD I showed prolonged ES2 latency under Erotica, and their perceived happiness and sadness intensities were negatively correlated with the respective ES2 durations, while BD II showed prolonged ES2 latencies under Disgust and Happiness, and shortened ES2 durations under Disgust, Happiness and Sadness. Moreover, ES2 duration under Sadness was significantly shorter in BD II than that in BD I. The cortico-brainstem inhibitory dysfunctions in BD I and BD II was different, and this difference was independent of the patient's ongoing emotions. Our study thus provides some hints to distinguish the two types of bipolar disorders.